2007
DOI: 10.1074/jbc.m707083200
|View full text |Cite
|
Sign up to set email alerts
|

CaMKIIδ Isoforms Differentially Affect Calcium Handling but Similarly Regulate HDAC/MEF2 Transcriptional Responses

Abstract: The ␦ B and ␦ C splice variants of Ca 2؉ /calmodulin-dependent protein kinase II (CaMKII), which differ by the presence of a nuclear localization sequence, are both expressed in cardiomyocytes. We used transgenic (TG) mice and CaMKII expression in cardiomyocytes to test the hypothesis that the CaMKII␦ C isoform regulates cytosolic Ca 2؉ handling and the ␦ B isoform, which localizes to the nucleus, regulates gene transcription. Phosphorylation of CaMKII sites on the ryanodine receptor (RyR) and on phospholamban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
172
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 188 publications
(187 citation statements)
references
References 51 publications
8
172
2
5
Order By: Relevance
“…Mef2c cardiac transcription factor expression in CPCs supports progression of myocyte progenitor precursor cells in to cells of the cardiomyogenic lineage (36). Additionally, CaMKII␦B overexpression is known to enhance the up-regulation of Mef2c to promote growth and maturation of cardiomyocytes (18). As expected, Mef2c gene expression in CPCe␦B was increased and is consistent with elevated protein expression during basal cell culture conditions compared with CPCe (Fig.…”
Section: Camkii␦b Overexpression In Cpcs Enhances Expression Of Pro-ssupporting
confidence: 68%
See 2 more Smart Citations
“…Mef2c cardiac transcription factor expression in CPCs supports progression of myocyte progenitor precursor cells in to cells of the cardiomyogenic lineage (36). Additionally, CaMKII␦B overexpression is known to enhance the up-regulation of Mef2c to promote growth and maturation of cardiomyocytes (18). As expected, Mef2c gene expression in CPCe␦B was increased and is consistent with elevated protein expression during basal cell culture conditions compared with CPCe (Fig.…”
Section: Camkii␦b Overexpression In Cpcs Enhances Expression Of Pro-ssupporting
confidence: 68%
“…G, quantitation of ␣-smooth muscle actin represented as a fold change relative to CPC sh-Ctrl in GM and after normalizing to GAPDH. MEF2 and serum response factor elements (18,19). Inactivation of Class IIa HDACs by CaMKII and protein kinase D promotes shuttling of HDAC4 from the nuclear compartment by the chaperone 14-3-3 (28,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the initiation of cardiac hypertrophy in adult hearts requires at least nuclear export of the HDACs and/or nuclear import of NFAT-like TFs. Studies in the past two decades have established that nuclear export of class II HADCs (HDAC-4, -5, -7, -9) is primarily mediated by phosphorylation catalyzed by the HDAC kinases including Ca 2ϩ / calmodulin-activated kinase II (CaMKII␦) (18) and protein kinase D1 (PKD1, known as PKC) (19). In comparison, activation of NFATs is achieved by CaN-catalyzed dephosphorylation (20).…”
Section: Pathological Cardiac Hypertrophy (Pch)mentioning
confidence: 99%
“…Although the intracellular targeting of protein kinase A to the effectors is being unraveled, little is known about the targeting of CaMKII activity, which is ubiquitously expressed and serves important roles in calcium signaling to guide synaptic transmission (2,5,6), gene transcription (7), cell growth (8), and excitation-contraction coupling (9 -11). Although four different isoforms of CaMKII (␣, ␤, ␦, and ␥) are expressed in a tissuespecific manner, cardiac tissue is shown to have predominance of CaMKII␦ C (cytosolic) and CaMKII␦ B (nuclear) isoforms, which serve roles in excitation-contraction coupling and cell growth, respectively (7,12). Studies have also revealed a significant level of a muscle-specific CaMKII ␤ isoform (CaMKII␤ 4 ) in skeletal and cardiac muscle (11,(13)(14)(15).…”
mentioning
confidence: 99%